Pengembangan Potensi Desa menjadi Desa Wisata di Desa Kelor, Kecamatan Karangmojo, Kabupaten Gunungkidul - Pratama, Yohanes Mario (Jurnal Atma Inovasia, 2022)
Kuliah Kerja Nyata (KKN) at Universitas Atma Jaya Yogyakarta in the era of the Covid-19 pandemic was carried out online, in other words this year's KKN was carried out without directly engaging in the community or what is called KKN Society 5.0. This activity aims to increase the level of student awareness of social aspects an also to increase motivation and knowledge into the potential development of the surrounding community. Group 39, unit H conducted the KKN in Kelor Village, Karangmojo District, Gunung Kidul Regency. Group 39 had a work program to develop e-books and videos about the potential of Kelor Village regarding the development of Kali Talang and Kali Klepu into tourist villages. In addition, group 39 developed an e-book and video on processing leaves, stems and roots from teak trees. The data collection method is done by collecting (secondary) data, then study it more systematically. This work program is expected to be able to attract tourists so that it can advance Kelor Village.